Supply chain analysis for standard and customized products with postponement. (February 2022) - Zheng, Meimei; Shi, Xiaoqian; Pan, Ershun; Wu, Kan
Highlights: Decisions in supply chains with standard and customized products are optimized. The condition when a manufacturer offers standard and customized products is derived. The retailer's first order decision is invariant to customized products' parameters. A cost-sharing contract is designed to realize supply chain coordination. Abstract: We analyze optimal production and order decisions for standard and customized products in a manufacturer-retailer system, whereby the retailer is offered two order opportunities by the manufacturer. Standard products are produced in make-to-stock fashion, whereas customized products are produced using a postponement strategy. In the decentralized system, the retailer's first order decision is independent of the parameters of customized products. Notably, it is not always profitable for the manufacturer to produce standard products or customized products. We derive the conditions in which the manufacturer is willing to produce both kinds of products or only one kind of product. A cost-sharing contract is designed to coordinate the manufacturer's and retailer's decisions in the supply chain with both standard and customized products. The results show that, with coordination, the contract can render both the manufacturer and retailer to obtain better profits.